Applications of Laser in the Medical Field - sarhan kareem, Abd al sattar; Hamza, Razzaq Sahib; sadeq hamzah, Hamzah; Jassim, Hussein Talib; Abed, Haneen Hayder (American Journal of Botany and Bioengineering, 2025)
Laser technology has revolutionized the medical field by offering precise, minimally invasive, and highly controllable tools for both diagnostics and therapeutic interventions. Despite its widespread integration into ophthalmology, dermatology, oncology, dentistry, and surgery, a comprehensive understanding of laser-tissue interaction across different systems and optimized protocols for treatment remain limited. This study presents a multi-disciplinary review of various laser types—including CO₂, Nd:YAG, diode, and argon lasers—and evaluates their applications through documented clinical procedures, historical development, and current innovations. The findings underscore the importance of tailoring laser parameters to specific medical contexts for maximal efficacy and minimal side effects. The implication of this review is to highlight the growing necessity for standardized training, expanded clinical trials, and further research into laser-based therapies, particularly in emerging areas such as photodynamic therapy and minimally invasive oncology. Laser medicine continues to evolve as a cornerstone of 21st-century precision healthcare.